1996
DOI: 10.1007/bf00168638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of basic fibroblast growth factor and ganglioside GM1 on neuronal survival in primary cultures and on eight-arm radial maze task in adult rats following partial fimbria transections

Abstract: The effects of basic fibroblast growth factor (bFGF) and ganglioside GM1 (GM1) were evaluated alone and simultaneously in two types of experiments. First, the neuronal survival of primary culture neurons from fetal rat brain was measured. Then, performance on radial maze task in adult male rats following bilateral partial Fimbria-Fornix transections (F-F lesion) was tested. In primary culture neurons, bFGF (1-10 ng/ml) supported the neuronal survival from three regions (hippocampus, cortex and septum) of embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In vivo studies conducted by Fong et al (1995) showed enhancement of ChAT activity in aged rats after intraperitoneal administration of GM1. GM1 combined with basic ® broblast growth factor also improved memory in lesioned rats (Iwashita et al 1996). In addition, recovery of motor function after spinal cord injury by GM1 has been shown (Geisler et al 1991).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In vivo studies conducted by Fong et al (1995) showed enhancement of ChAT activity in aged rats after intraperitoneal administration of GM1. GM1 combined with basic ® broblast growth factor also improved memory in lesioned rats (Iwashita et al 1996). In addition, recovery of motor function after spinal cord injury by GM1 has been shown (Geisler et al 1991).…”
Section: Discussionmentioning
confidence: 96%
“…Casamenti et al (1989) also demonstrated that GM1, when injected into the brain of rats with unilateral lesion of the nucleus basalis, alleviate cholinergic de® cits by protecting the cholinergic neurons of the nucleus basalis from ibotenic neurotoxicity. GM1 has also been shown to potentiate the effects of neurotrophic factors such as nerve growth (Garafalo and Cuello 1994) and basal ® broblast growth (Iwashita et al 1996) in enhancing ChAT activity and in improving memory of rats with partial ® mbria transections.…”
mentioning
confidence: 96%
“…GM1 levels in CSF has been shown to improve day-to-day activity in AD ( Augustinsson et al, 1997 ), and it increases choline acetyl esterase activity (ChAT) ( Fong et al, 1995 ). It potentiates the effects of neurotrophic factor ( Facci et al, 1990 ; Ferrari et al, 1993 ; Garofalo and Cuello, 1994 ) and basic fibroblast growth factor ( Iwashita et al, 1996 ). GM1 has been shown to reduced amyloid-β toxicity ( Kreutz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%